Do exchangeable hydrogens affect the evaluation of partial mycoheterotrophy in orchids? Insights from δ2H analysis in bulk, α-cellulose, and cellulose nitrate samples - Yagi, Ryuta (The New phytologist, 2024)
© 2024 The Author(s). New Phytologist © 2024 New Phytologist Foundation.